Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1029/2020gl089346
|View full text |Cite
|
Sign up to set email alerts
|

Momentum and Energy Predict the Backwater Rise Generated by a Large Wood Jam

Abstract: Wood reintroduction is now considered an important aspect of stream restoration, due to ecohydraulic benefits associated with wood presence. Channel‐spanning wood jams create an upstream backwater, increasing flow heterogeneity, sediment deposition, and ecological productivity, but also flood risk. Backwater rise prediction is necessary to evaluate flood hazards in hydraulic models, improve design of engineered logjam projects, and compare jam effects across river systems. We present experimental results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 53 publications
6
77
0
Order By: Relevance
“…Water approaching a jam with a lower gap partitions between the porous jam and the gap beneath the jam. Flow exiting the jam adopted an elevated height hj>a (Figure 2) similar to previous observations of flow through channel‐spanning jams without a lower gap (Follett et al., 2020). Negligible exchange of flow between the jam and gap sections was visually observed from injections of rhodamine dye.…”
Section: Theorysupporting
confidence: 87%
See 3 more Smart Citations
“…Water approaching a jam with a lower gap partitions between the porous jam and the gap beneath the jam. Flow exiting the jam adopted an elevated height hj>a (Figure 2) similar to previous observations of flow through channel‐spanning jams without a lower gap (Follett et al., 2020). Negligible exchange of flow between the jam and gap sections was visually observed from injections of rhodamine dye.…”
Section: Theorysupporting
confidence: 87%
“…Upstream water depth h0 was measured Lcv=1 m upstream of jam leading edge. Discharge through the jam qj calculated for yellow control volume extending from x=xa to xj and z=a to h0,hj (Follett et al., 2020). Discharge through the gap qa estimated for blue control volume x=x0 to xa and z=0 to h0, accounting for discharge through the jam.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The random variation in β i between mixtures, repetitions, volume of LW and water discharge is higher than the eventual effect of fine material. Follett et al (2020) recently demonstrated that head losses were related to the projected area of the material (coarse and fine) constituting the jam. Our fine material was not fine enough to percolate through the accumulation to densify it and to increase the projected area as leaves and fine organic matter would.…”
Section: First Step Toward Generalizationmentioning
confidence: 99%